Polystichum zhijinense (subg. Haplopolystichum; Dryopteridaceae), a new cave species of Polystichum from Guizhou, China - Duan, Yi-Fan; Kropf, Matthias; Zhang, Li-Bing (Phytotaxa, 2017)
A new fern species, Polystichum zhijinense, a member of P. subg. Haplopolystichum (Dryopteridaceae), is described and illustrated from Guizhou Province in Southwest China. Polystichum zhijinense is somehow similar to P. fengshanense in having pinnae oblong and entire or shallowly repand (not aristate-spinulose on the margin), but differs in the shape of the pinna apex, the morphology of microscales, and the sorus distribution. Polystichum zhijinense was found at a cave entrance and is currently known from one population only and thus is classified as Critically Endangered (CR) following IUCN Red List criteria.